Formulation of Salacca zalacca Fruit Peel and Citrus nobilis Peel Extract as an Alternative for Environmentally Friendly Tissue Paper - Dinda Laura El Islami; Lina Nur Agustina; Ananda Dyah Khairunnisa; Rizki Arumning Tyas (Universitas Satya Terra Bhinneka, 2025)
Tissue paper is commonly used as a water substitute for cleaning, made from pulp with cellulose as the primary raw material. Salacca zalacca peel contains cellulose that can serve as an adsorbent capable of absorbing heavy metals in wastewater. With a cellulose content of 25.8483%, Salacca zalacca peel holds great potential as a raw material for producing environmentally friendly tissue paper. This study focuses on formulating Salacca zalacca peel waste with the addition of aromatherapy from Citrus nobilis peel extract to create eco-friendly tissue. The objectives of this research are to (1) identify the formulation process, (2) determine the best formulation, and (3) evaluate the quality of the eco-friendly tissue produced. The research uses a true experimental method, and data analysis includes organoleptic tests, tissue paper quantity tests, and biodegradability tests. The findings indicate that the best formulation is achieved with a 70% NaOH concentration, resulting in good physical quality tissue, characterized by a smooth texture, pale yellowish-brown color, and a dominant citrus scent. From a biodegradability perspective, all samples showed excellent degradation rates, confirming their environmentally friendly nature. This research contributes to sustainable environmental practices by offering an alternative to traditional wood-based tissue paper. Utilizing agricultural waste such as Salacca zalacca peel not only reduces the pressure on forest resources but also minimizes environmental pollution. The incorporation of natural aromatherapy further enhances the product's eco-friendly credentials, promoting a sustainable approach to tissue production that aligns with global efforts to reduce deforestation and encourage the use of renewable materials. In conclusion, the study demonstrates the feasibility of using Salacca zalacca peel and Citrus nobilis peel extract, combined with corn husk, as raw materials for producing eco-friendly tissue paper.